Drawing light from the pandemic: Rethinking strategies for health policy and beyond. Issue 1 (January 2022) - Forman, Rebecca; Azzopardi-Muscat, Natasha; Kirkby, Victoria; Lessof, Suszy; Nathan, Naomi Limaro; Pastorino, Gabriele; Permanand, Govin; van Schalkwyk, May CI; Torbica, Aleksandra; Busse, Reinhard; Figueras, Josep; McKee, Martin; et al.
Highlights: The catastrophic impacts of COVID-19 were preventable, but we were underprepared. The Commission's final report provides actionable recommendations to achieve seven objectives. One health approaches, health system investment and better governance structures are all needed. Efforts to minimize systemic inequalities and improve innovation incentives must be increased. Health governance in Europe must be reinforced and the role of and funding for WHO strengthened. Abstract: The COVID-19 pandemic is a catastrophe. It was also preventable. The potential impacts of a novel pathogen were foreseen and for decades scientists and commentators around the world warned of the threat. Most governments and global institutions failed to heed the warnings or to pay enough attention to risks emerging at the interface of human, animal, and environmental health. We were not ready for COVID-19, and people, economies, and governments around the world have suffered as a result. We must learn from these experiences now and implement transformational changes so that we can prevent future crises, and if and when emergencies do emerge, we can respond in more timely, robust and equitable ways, and minimize immediate and longer-term impacts. In 2020–21 the Pan-European Commission on Health and Sustainable Development assessed the challenges posed by COVID-19 in the WHO European region and the lessons from the response. The Commissioners have addressed health in its entirety, analyzing the interactions between health and sustainable development and considering how other policy priorities can contribute to achieving both. The Commission's final report makes a series of policy recommendations that are evidence-informed and above all actionable. Adopting them would achieve seven key objectives and help build truly sustainable health systems and fairer societies.